Trends in hypertension and hypertension treatment in primary care in general practices in Germany between 2013 and 2022 - Kostev, Karel; Krieg, Sarah; Jacob, Louis (Frontiers in Cardiovascular Medicine, 2024)
Background There is a scarcity of data on the epidemiology of hypertension and its treatment in Germany in recent years. Objectives The present study aimed to investigate trends in the number of adults diagnosed with hypertension and those being prescribed antihypertensive drugs each year in general practices from this country between 2013 and 2022. Methods This retrospective cohort study used data of adults aged ≥18 years continuously collected from 336 general practices in Germany (IQVIA) during 2013–2022. The diagnosis of hypertension and the prescription of antihypertensive drugs were coded using the ICD-10 and the EphMRA classification, respectively. Covariates included the total number of patients, mean (SD) age of patients, and proportion of women per practice. Trends in hypertension diagnosis and treatment were studied using linear regression models. Results The mean (SD) total number of patients per practice ranged from 2,235 (1,055) in 2013–2,845 (2,090) in 2021 (p-value < 0.001). The mean (SD) age of patients per practice was between 48.4 (21.5) and 50.5 (21.4) years, while the proportion of women was 52.1%–53.9% (p-values < 0.001). After adjusting for covariates, there was a significant decrease in the number of patients diagnosed with hypertension (beta coefficient = −7.91, p-value < 0.001) and treated with any antihypertensive drug per practice per year between 2013 and 2022 (beta coefficient = −5.40, p-value < 0.001). Conclusion This study identified decreasing trends in the diagnosis and treatment of hypertension in general practices in Germany in the last decade. These data may suggest that the prevention of hypertension has improved in this country in recent years.